Välkommen : vackrare infart till Vilhelmina - Nilsson, Anna (SLU/Dept. of Urban and Rural Development, 2006)
The purpose of this thesis is to show how a good approach can be designed, focusing on the southern approach to the Swedish town Vilhelmina. Prior to the car being part of everyday life, the approach was a road where the town showed itself from the very best side. When the amount of traffic increased, so did noise and other disturbances, and as a consequence industrial areas replaced the residential buildnings at the approaches. Today, the pendulum is turning back and in recent years the approach is regarded as a place to introduce the town. The approach is also the place where cars should slow down from the speed of the main road to the speed of the city. To design a road, there are many aspects to consider. In this work, I focus on safety, vegetation and profiling the town. Traffic safety is an important issue and roads are subject to extensive regulations. Designing the road and its surroundings effects the behaviour of the road-users. A beautiful road reduces velocities and lowers the risk of accidents. Vegetation is an essential part of the design. In addition to closing the surroundings or opening up to reveal views, vegetation also helps to create a more varied road environment, which keeps drivers alert. With the renewed interest in the design of approaches, several towns begin to realise the possibilities of profiling themselves through the approach. A design which clearly shows which town you are entering and its interesting features, helps the road-users to remember the town and it might make them want to stop and pay it a visit. Vilhelmina is a small town and a municipality in northern Sweden. Though its area is extensive, the number of inhabitants is no more than 7 000, of which 5 000 live in the town. The eastern part of the municipality is made up of forests and bogs, while the Scandinavian mountain range extends through the western part. The lakes are numerous and in several of the rivers hydroelectric power stations have been built. In the past, hunting, fishing and reindeer-raising, and later ...